Language learners’ mental images of Korea: insights for the teaching of culture in the language classroom - Nikitina, Larisa; Furuoka, Fumitaka (Taylor & Francis, 2019)
People who learn a foreign language hold various mental images about the target language country, its culture and society. These images are recognised as a valuable source of information for developing the cultural component of a foreign language programme. However, explorations of mental images of Korea held by students enrolled in Korean language programmes are scarce. The current study addresses this gap. It explores images of Korea held by students learning Korean in a major public university in Malaysia. The country images that the students have were then assessed for prominence and favourability. It was found that the images of Korea were overwhelmingly positive and the most prominent of them pertained to Korea’s popular culture and cultural products. At the same time the findings revealed the need for a deeper knowledge of the target culture. Pedagogical implications concerning the development of the cultural component of the Korean language programme are discussed. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.